Strategi Kepala Sekolah Dalam Meningkatkan Kualitas Sekolah Melalui Pemenuhan Ruang Kelas Yang Memadai - Mahmudiyah, B. Zuroidatul (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2019)
The purpose of this study is to find problems in improving the quality of schools and find strategies that can be done by Principals to improve the quality of schools by fulfilling adequate classrooms. The method used in this study is qualitative. Data collection by observation, interviews, and documentation. Qualitative descriptive data analysis. The results of his research, namely (1) problems in improving school quality, namely the lack of adequate classrooms and (2) strategies that can be carried out by school principals to improve school quality by fulfilling adequate classrooms include: (a) inviting parents students to come to school aim to socialize (explain the problems that exist in the school about the lack of classrooms and the need to fulfill adequate classrooms and plans for the construction of adequate classrooms) and (2) establish partnerships with industry or private companies.